Intramolecular carbolithiation of alkynes: observation, mechanism, applications - Maddaluno, Jacques; Fressigné, Catherine; Durandetti, Muriel (Synlett)
The intramolecular carbolithiation of alkynes is a useful cyclisation reaction that gives stereoselectively access to functionalized alkenes. This reaction is supposed to proceed through a syn-addition mechanism. We show in this account that the interaction between the lithium cation and the substituent on the propargylic position (or directly on the triple bond) can derail this process and afford selectively the anti-addition product. The set of results presented in this account, both experimental and theoretical, suggests that the stereochemical outcome of the addition can be predicted with success.